A new species of Nothobrya Arlé, 1961 (Collembola: Entomobryidae) from Brazil and notes on key characters for Nothobryinae taxonomy, with an identification key to the species of the subfamily - Nunes, Rudy Camilo; Bellini, Bruno Cavalcante (Zootaxa, 2019)
A new species of Nothobrya Arlé is described and illustrated. The specimens were collected in Serra da Capivara National Park and its vicinities, Caatinga Biome, Piauí State, Brazil, from soil and leaf litter samples. Nothobrya sertaneja sp. nov. differs from the two previously described species of the genus, N. arlei Silveira & Mendonça and N. schubarti Arlé, by antennae with 4–5 antennomeres (6 in N. arlei and N. schubarti); metatrochanteral organ with 7–13 spine-like chaetae (15 in N. arlei and 3–4 in N. schubarti); tenaculum with 2–3 smooth chaetae on corpus (4 ciliated chaetae in N. arlei and 2 chaetae with unclear morphology in N. schubarti); and inner unguis with 2 basal paired teeth, 1 median and 1 apical tooth (2 basal paired, 1 median and 2 lateral teeth in N. arlei and 2 basal paired and 0–1 unpaired median tooth in N. schubarti). We present herein the first complete and labelled dorsal chaetotaxy description of the genus and the entire subfamily, including the S-chaetotaxy of the tergal segments. Finally, we also provide a new diagnosis to Nothobrya, plus an identification key to species of Nothobryinae.